2021
DOI: 10.1002/jcu.23056
|View full text |Cite
|
Sign up to set email alerts
|

Breast implant seroma: A SARS‐CoV‐2 mRNA vaccine side effect

Abstract: Fluid collection surrounding breast implants, called seroma, is a frequent issue that has diverse etiologies. We describe a 48‐year‐old woman with an acute onset of bilateral breast swelling occurring 5 years after aesthetic surgery and 10 days after a second SARS‐CoV‐2 mRNA vaccine dose. At breast ultrasound, we found an abundant bilateral peri‐implant seroma. Our patient noticed symptom improvement 48 h after nonsteroidal anti‐inflammatory drug treatment, complete disappearance of symptoms after 10 days with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
4
0
5
Order By: Relevance
“…In the cases we counted, seroma, swelling, and pain were the most common symptoms. If patients with breast prosthesis develop seroma after COVID‐19 vaccination, we can make a differential diagnosis of other possible diseases such as breast implant‐associated anaplastic large cell lymphoma (ALCL) 84 . The available cases showed that symptoms were not significantly correlated with the timing of implant surgery and the texture of implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cases we counted, seroma, swelling, and pain were the most common symptoms. If patients with breast prosthesis develop seroma after COVID‐19 vaccination, we can make a differential diagnosis of other possible diseases such as breast implant‐associated anaplastic large cell lymphoma (ALCL) 84 . The available cases showed that symptoms were not significantly correlated with the timing of implant surgery and the texture of implants.…”
Section: Discussionmentioning
confidence: 99%
“…If patients with breast prosthesis develop seroma after COVID-19 vaccination, we can make a differential diagnosis of other possible diseases such as breast implant-associated anaplastic large cell lymphoma (ALCL). 84 The available cases showed that symptoms were not significantly correlated with the timing of implant surgery and the texture of implants. The implant should be removed as soon as possible in cases where conservative treatment has failed.…”
Section: Diagnosis and Treatmentmentioning
confidence: 97%
“…Acute onset of breast implant seroma has been demonstrated after receiving COVID vaccine, which was attributed to the postvaccination immune response. 48 These reactions are believed to be the result of vaccine adjuvants, which lead to autoimmune/inflammatory syndrome induced by adjuvants (ASIA) 49 ; however, the interaction between the skin ACE-2 receptors and the vaccine's spike protein can also be an underlying mechanism. 36 Most of the vaccine-induced reactions in previously cosmetically manipulated areas are tardive reactions, which take place with delay, usually within 10 days after vaccination.…”
Section: Covid Vaccine-rel Ated Adver S E E Vents In Ind Ividual S Un...mentioning
confidence: 99%
“…Moreover, capsular fibrosis and other esthetic purposes are the reason of breast implant surgery. Acute onset of breast implant seroma has been demonstrated after receiving COVID vaccine, which was attributed to the postvaccination immune response 48 …”
Section: Covid Vaccine‐related Adverse Events In Individuals Undergoi...mentioning
confidence: 99%
“…Las vacunas producen la activación específica e inespecífica del sistema inmunológico, incluyendo células inmunológicamente activas como macrófagos, linfocitos T y miofibroblastos que se encuentran alrededor de los implantes mamarios, con reacciones inflamatorias. [44][45][46][47] El objetivo de este trabajo es identificar el impacto que ha tenido el linfoma y la CO-VID-19 en la cirugía de aumento mamario, en la elección del tipo de implantes y en la incidencia de complicaciones.…”
Section: Introductionunclassified